Identifying the effects of climate change on discharge and sediment transport in a typical alpine basin - Ya Zhou; Lei Huang; Liangwen Huang; Jiafu Liu (International Journal of Sediment Research)
Global-scale changes in precipitation and temperature lead to regional variations in the hydrologic cycle. Understanding the impacts of climate change on discharge and sediment processes is crucial for effective watershed management, especially in alpine regions. A hydrologic modeling framework was established for the Yarlung Tsangpo River (YTR) watershed, the largest and longest river system on the Tibetan Plateau, which integrates the Soil and Water Assessment Tool (SWAT) with global climate models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6). The results highlight the importance of temperature in influencing hydrological elements during snowmelt periods in the northeastern and western parts of the YTR basin and precipitation across the entire basin during rainy periods. Compared with discharge, sediment flux has been more sensitive to climate change over the past four decades. The annual mean discharge at the downstream station is projected to decrease by −3.60% ± 2.68% in the near-term period (2025–2035) but increases by 4.18% ± 3.30% in the mid-term period (2040–2050) relative to the baseline value of 2000–2014. Moreover, the annual mean sediment flux is expected to change by −1.06% ± 2.98% in the near-term period and by 8.30% ± 3.65% in the mid-term period. These results will enhance adaptive management and policy-making for alpine regions.